Open throat - Hoke, Henry, 1983- (MCD / Farrar, Straus and Giroux, 2023)
A queer and dangerously hungry mountain lion lives in the drought-devastated land under the Hollywood sign. Lonely and fascinated by humanity's foibles, the lion spends their days protecting a nearby homeless encampment, observing hikers complain about their trauma, and, in quiet moments, grappling with the complexities of their gender identity, memories of a vicious father, and the indignities of sentience. When a man-made fire engulfs the encampment, the lion is forced from the hills down into the city the hikers call "ellay." As the lion confronts a carousel of temptations and threats, they take us on a tour that spans the cruel inequalities of Los Angeles and the toll of climate grief. But even when salvation finally seems within reach, they are forced to face down the ultimate question: Do they want to eat a person, or become one?